Low friction, elastomer-containing copolyimides. (February 2013) - Wohl, Christopher J.; Chen, Lillian; Lin, Yi; Connell, John W.
Novel copoly(imide butadiene)s and copoly(imide butadiene acrylonitrile)s were synthesized from amine-terminated butadiene oligomers, amine-terminated butadiene acrylonitrile oligomers, and aromatic dianhydrides and diamines. The copoly(amide acid)s were synthesized in a mixture of N -methyl-2-pyrrolidinone and toluene and were subsequently cast into thin films. The films were cyclodehydrated under a nitrogen atmosphere with a final cure at 250°C to minimize thermal degradation of the aliphatic components. Free-standing films of the copolymers exhibited reduced optical transparency, mechanical properties, water contact angle values, and sliding coefficients of friction when compared with homopolyimide films. These results indicated both bulk and surface phase segregation. Surface phase segregation was observed using atomic force microscopic imaging and was related to insufficient elastomer wetting of the casting surface. The detailed results of this study are discussed herein.